New austral-most records of the genus Heterostylum Macquart (Diptera: Bombyiliidae) in Argentina - Torretta, Juan P.; Haedo, Joana P.; Marrero, Hugo J.; Lamas, Carlos J.e. (Zootaxa, 2021)
Bee flies of the genus Heterostylum Macquart are medium-sized species (10–15 mm) characterized primarily by a robust body covered with long pile and by an indented hind margin of the eye (Cunha et al. 2007). There are several studies on the immatures of some species of Heterostylum (Bohart et al. 1960; Yeates & Greathead 1997), which are considered ectoparasites of fossorial solitary bee larvae and pupae (Yeates & Greathead 1997).